Perspectives of Women Giving Birth during the COVID-19 Pandemic and Their Nurses. Issue 3 (May 2022) - Callister, Lynn Clark
Abstract : The prolonged COVID-19 global pandemic has had a profound effect on the lived experiences of birthing women and their nurses. Our global health and nursing expert, Dr. Callister, reviews some of the recent data on how women giving birth and maternity nurses are coping with the changes in care conditions due to the pandemic.